Restoring and holding on to beauty : the role of aesthetic relational values in sustainable development - Swartz, Moshe E. Ncilashe (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Public Management and Planning))--University of Stellenbosch, 2010.